2019
DOI: 10.25304/rlt.v27.2296
|View full text |Cite
|
Sign up to set email alerts
|

Putting design into practice: An investigation of TPACK scores of lecturers in a networked institution

Abstract: Demand for blended and online learning environments is increasing and concurrent with this is the changing competencies required for teachers to be able to facilitate learning in both face-to-face and virtual space. The Technological Pedagogical Content Knowledge (TPACK) is a measure of teachers pedagogical, content and technical knowledge and their skill to embed technology in practice. Using the TPACK framework, this study explores the relationship between technical skills, learning design and how these rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(42 reference statements)
1
5
0
2
Order By: Relevance
“…This suggestion is supported by Li et al (2021) findings that lecturers perceived that their technology-related knowledge is not well developed compared to their CK, PK, and PCK. In addition, it is also in line with Fabian et al (2019) findings that the lecturers perceived their TK as less developed than their PCK.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This suggestion is supported by Li et al (2021) findings that lecturers perceived that their technology-related knowledge is not well developed compared to their CK, PK, and PCK. In addition, it is also in line with Fabian et al (2019) findings that the lecturers perceived their TK as less developed than their PCK.…”
Section: Discussionsupporting
confidence: 86%
“…Previous research on TPACK as a framework focused more on teacher education and teachers at kindergarten and schools. A few studies have explored TPACK at the tertiary level (Fabian et al, 2019). Benson and Ward (2013), through conducting a qualitative case study with three faculty members, found that high TK alone is not enough for developing TPACK, and a high level of PK is the enabling force in the development of this knowledge.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…More concretely, teachers should learn about ways to use technology to encourage students to move from more passive learning activities (mostly digital presentations) to constructive learning activities (e.g., constructing concept maps) and interactive learning activities (e.g., create an explanation video in small groups). Consequently, higher education teachers should be supported by their institution in various ways (Fabian et al, 2019). One promising approach might be to offer professional development in order to develop teachers' TPACK.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien el conocimiento pedagógico es fundamental, un conocimiento tecnológico estándar es un requisito. Según Fabian et al (2019), los docentes con una puntuación más alta de TPACK -el conocimiento tecnológico, pedagógico y de contenido según el modelo de Koehler y Mishra (2005)-, tendían a aplicar diseños más interactivos.…”
Section: Introductionunclassified